2013
DOI: 10.1371/journal.pone.0062044
|View full text |Cite
|
Sign up to set email alerts
|

Exopolymer Diversity and the Role of Levan in Bacillus subtilis Biofilms

Abstract: Exopolymeric substances (EPS) are important for biofilm formation and their chemical composition may influence biofilm properties. To explore these relationships the chemical composition of EPS from Bacillus subtilis NCIB 3610 biofilms grown in sucrose-rich (SYM) and sucrose-poor (MSgg and Czapek) media was studied. We observed marked differences in composition of EPS polymers isolated from all three biofilms or from spent media below the biofilms. The polysaccharide levan dominated the EPS of SYM grown biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 66 publications
(80 reference statements)
1
106
3
Order By: Relevance
“…It has been demonstrated that in sucrose-rich growth media, Bacillus subtilis produces copious amounts of levan, resulting in thick floating biofilms (9). Levan is the main component of such biofilms and comprises~95% of the extracellular matrix mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that in sucrose-rich growth media, Bacillus subtilis produces copious amounts of levan, resulting in thick floating biofilms (9). Levan is the main component of such biofilms and comprises~95% of the extracellular matrix mass.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it may be loosely attached to the cell as an extracellular polymeric substance (EPS), which gives bacterial colonies their typical mucoid morphology (8). Recently, it was reported that levan is an important structural component of microbial biofilms, playing a stabilizing role in their formation and maintenance (9,10). Since levan is an extremely soluble (i.e., up to 60% w/v), low-viscosity polymer, it is surprising that it can stabilize biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…Again, this nding was unexpected as tasA biolm pellicles formed on MSgg medium are considerable decreased in biolm height compared to pellicles generated by the wild-type strain. 52 Whereas the absence of the TasA protein leads to an increased biolm height for biolm colonies grown on LB agar plates, the absence of the BslA protein led to a decrease of the nal biolm height by $30%. A similar result was obtained for biolm colonies formed by the epsA-O mutant strain.…”
Section: Matrix Composition Determines the Dimensions Of Mature Ncib mentioning
confidence: 99%
“…1). Inulin principally occurs in dicot plants, however, levan more commonly occurs in monocot plants and bacteria (Dogsa et al 2013;Valluru and van den Ende 2008). In plants, inulin is biosynthesized from sucrose by a two-step reaction.…”
Section: Introductionmentioning
confidence: 99%